Faktor Fisik dan Psikologis Prestasi Cabang Olahraga Petanque - Amalia, Bonita; Nurkholis, Nurkholis; Sulistyarto, Soni (UIR Press, 2019)
This study aimed to know dominant elements of physical and psychological factor in Petanque. Both of these factors are closely integrated in sport. This research was conducted as quantitative approach with descriptive-correlation design. The subjects of this study were athletes of UNESA, athletes of Lamongan, and coaches who came from all over Indonesia. For data analysis, it used Partial Least Square analysis. The result of this study can be seen from two parts. First result shows that physical factor that can be identified as dominant factor of Petanque consists ofwrist flexibility and aerobic parity element and for psychological factor, there are anxiety and self-confidence element. Second result shows that the dominant elements of physical and psychological factors of Petanque arephysiology, biomotor, and psychology which 97,6% dominantly affect Petanque.